Knowledge of the Mothers toward Sanitation and Hygiene in relation to Childhood Gastroenteritis in Babylon Province - Sijal Fadhil Farhood Al Joborae1 , Fadhil Farhood Mekki Al Joborae2 , Sura Falah Abdul Hadi Al-Jubba (Institute of Medico-legal Publications Pvt Ltd, 2020)
The negative impact of gastroenteritis in those aged 5 or less in Babylon Province in Central Iraq cannot beunderestimated as it is a serious impediment to the wellbeing and cognitive development of children anda cause of unnecessary death in this resource-strained region of the Middle Eastern country. In this regiondiarrhea is an important clinical presentation at primary health care institutions and other health affiliatedcentres, stands out as a leading cause of admission to many of the emergency hospital wards in Babylon,and a serious and ironically, often reversible cause of loss of precious lives. Regional attitudes in the MiddleEuphrates Region about causes that lead to childhood gastroenteritis vary from rural and urban localities andeven from townships, a cultural issue that is true for most provinces of Iraq.Aim of the study: 1-To study the social and demographic aspects related to sanitation and personal hygieneregarding childhood diarrhea in Babylon Province.2- To determine the local knowledge, of women and care givers about childhood diarrhea.Patients and methods: This cross sectional work was carried in Babylon Province, Iraq. A total 408respondents attending primary health care institutions and pediatric clinics for treatment of diarrhea , duringthe period from first of January 2019 to the first of May 2019.Results and Conclusions: In Babylon Province outbreaks of diarrhea tend to be noticed early in life priorto first year of life despite the fact that around three quarters of infants who contracted gastroenteritis werein compliance with Rota Vaccine timetable schedule. Seven out of ten women were fully knowledgeable ofthe importance immunization against Rota virus and its vital role in reduction of the risk of gastroenteritis.When their children contract diarrhea, a percentage shy of 66% said that they would seek paediatric medicalattention .Respondents whose infants were affected tend to be mostly urban, in their teenage years and lackedproper education. There is a remarkable lack of adequate knowledge about ways of contracting childhoodgastroenteritis.